The Influence Of Borneo Puzzle Game Based On Education Game Towards The Level Of Concentration Of Chidren With Attention Deficit Hyperactivity Disorder (Adhd) In The Extraordinary School Of Pontianak City - Ratri, Maya Masita; Wardhani, Puspa; Triyani, Irma (Politeknik Kesehatan Kemenkes Mamuju, 2023)
ADHD is a mental disorder characterized by attention deficit, hyperactivity and impulsivity so having difficulty concentrating. One of the efforts to increase concentration is giving play therapy Borneo Puzzle based on education game. This study was conducted in the Extraordinary School of Cahaya Bangsa, Bina Anak Bangsa, Kinasih and Autism West Kalimantan. This study aimed to determine the effect of Borneo Puzzle game based on education game towards the level of concentration of chidren with ADHD. The study methods used quasi experimental with population of 20 Elementary Students with total sampling technique. 10 students were given Borneo Puzzle based on education game and 10 students were given a conventional puzzle for 6 consecutive days. We used Concentration Grid Exercise as an instrument, statistic test analyzed with Paired t-test dan Independent t-test. Paired t-test results showed p = 0,000 in the intervention group and p = 0,001 in the control group (p value < 0,05) which means that Borneo Puzzle game based on education game and conventional puzzle had a significant effect on the concentration level of ADHD children. The average difference of total score concentration level between before and after treatment in the intervention group was 4,60 (SD 2,45) greater than the control group which was 3,70 (SD 2,35), with Independent t-test results showed p value = 0,415 (p value > 0,05) shows no significant difference in the total score. Conclusion: there is an influence of Borneo Puzzle game based on education game towards the level of concentration of children with ADHD in the Extraordinary School Pontianak City in 2020. Borneo Puzzle game based on education game can be used as an alternative game model in play therapy to increase the concentration of children with ADHD.